ABOUT THE METHODOLOGY OF PREPARATION OF BASKETBALL PLAYERS FOR THE GAME 3 x 3 BASKETBALL - L. Petrov; M. Bonev (Trakia Journal of Sciences)
PURPOSE: In the preparation for competitions in 3 x 3 basketball some peculiarities in technical and tactical terms are observed. METHODS: In the study we used content analysis and sports pedagogical observation. RESULTS: Our observations showed that in attack the players are mainly looking for a pass from a teammate, fast shooting, mainly from the area behind the arc, inclusion in the fight for the ball bounced from the basket and a sharp transition to defence if the shooting is not successful. Interactions are short, often involving a pass, intersection or shelter, and long-range shooting. The main focus remains the individual game 1/1. CONCLUSIONS: Individual technical and tactical training and aggression are the factors that decide the success of the competitions. In the preparation for 3x3 basketball competitions to focus on: • The opening when passing between the players in case of aggressive defence; • Game 1/1; • Shooting behind the arc; • Pick and roll.